Cooperation of small and medium-sized enterprises with other supply chain participants in implementing the concept of green logistics - Zowada, Krzysztof; Niestrój, Krzysztof (Współpraca małych i średnich przedsiębiorstw z innymi uczestnikami łańcuchów dostaw we wdrażaniu koncepcji zielonej logistyki, 2019)
The concept of green logistics meets the expectations of various groups of stakeholders who, being aware of the negative impact of logistics processes on the natural environment, encourage enterprises to start implementing environmentally friendly solutions, thus ensuring the economic efficiency of these processes. The implementation of green solutions takes place in four stages and their advancement increases at each stage. The highest stages require cooperation with other enterprises. The article deals with the subject of undertaking this kind of cooperation by small and medium-sized enterprises in a supply chain. The aim is to identify which chain participants most often establish cooperation in the area of green logistics with these companies in Poland. It was found that the most intense cooperation takes place with a supply chain leader and suppliers. At the highest level of advancement a horizontal cooperation with competitors is also established
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 6, s. 249-260
Keywords: green logistics; green practice; supply chain; cooperation in supply chain; zielona logistyka; zielone praktyki; łańcuch dostaw; współpraca w łańcuchu dostaw